Characterizing Hydroxypropyl Guar - Borate Interactions with Model Tear Film Components - Cui, Yuguo (My University, 2010)
Hydroxypropyl guar (HPG) is an effective ingredient in lubricant eye drops used by patients with dry eye disease. The overall goal of the work described in this thesis is to understand the physical-chemical properties of HPG in the presence ofmodel surfaces and solutes with view to understanding the behavior of HPG in the tear film.
HPG behaviors are complex because borate ions bind to HPG, which converts nonionic HPG into anionic polyelectrolyte, RPG-borate. The borate binding constants are very low, meaning the charges on RPG-borate are labile. Another consequence ofweak binding is that the equilibrium electrolyte concentration with HPG-borate is relatively high. Mathematical models were developed to predict the structure of HPG-borate as functions of pH.
This thesis probes the question "When does HPG-borate behave as an anionic polyelectrolyte?" This work shows that HPG-borate exhibits deviant behaviors of an anionic polyelectrolyte: does not interact with cationic surfactants below the CMC; does not interact with lysozyme (cationic protein), and does not adsorb onto cationic liposomes. By contrast, anionic polyelectrolytes such as carboxymethyl guar display generic behaviors. On the other hand, HPG-borate forms polyelectrolyte complexes with cationic polyelectrolytes at low ionic strength and other work from our laboratory has shown that HPG-borate flocculates cationic polystyrene latex.
This complex range of RPG-borate behaviors was rationalized by proposing that the labile nature ofthe charge groups means that the charge density on RPG-borate is regulated by the local electrostatic environment. Near a cationic surface HPG-borate charge density increases whereas near an anionic surface the charge density is lower.
Anionic liposome interactions with HPG-borate were characterized. HPG concentrations close to clinical levels induced depletion flocculation ofthe anionic liposomes. This is the first example we have found depletion interactions were proposed for the tear film.
To summarize the main implications for the ophthalmic application of HPG are: 1) under ophthalmic conditions HPG-borate behaves as a nonionic water soluble polymer; 2) RPG-borate will adsorb onto hydrophobic domains but will not interact with lysozyme; 3) depletion interactions are important and have the potential to stabilize the lipid layer and destabilize emulsion droplets and other dispersed species in the tear film.
Keywords: chemical engineering; hydroxypropyl guar; borate interaction; tear film component